Attitudes and Commitment Toward Precautionary Measures Against COVID-19 Amongst the Jordanian Population: A Large-Scale Cross-Sectional Survey - Khatatbeh, Moawiah; Al-Maqableh, Hindya O.; Albalas, Samir; Al Ajlouni, Sara; A'aqoulah, Ashraf; Khatatbeh, Haitham; Kasasbeh, Mohammed A.; Khatatbeh, Ibdaa; Albalas, Rahaf; Al-Tammemi, Ala'a B. (Frontiers in Public Health, 2021)
Aims: This study aimed to (1) assess the non-pharmaceutical intervention (NPI) measures that were used by the Jordanian population against COVID-19, and (2) determine the sociodemographic and behavioral predictors of contracting COVID-19 with a focus on the utilization of personal precautionary measures. Methods: A descriptive questionnaire-based cross-sectional survey was used in this study. A structured web-based questionnaire was disseminated to the Jordanian community through social media platforms. Participants were asked a series of questions about socio-demographic characteristics, in addition to the knowledge, attitudes, and commitment towards using various personal precautionary measures (e.g., face mask, hand washing, social distancing) against the COVID-19. Data were analyzed using descriptive statistics, cross-tabulation, and binary logistic regression through SPSS®. Results: Responses from 7746 participants were included in our final analyses. Descriptive statistics showed that most participants (82.6%) believed that face mask protects against COVID-19. Around 69.5% of the participants were completely committed to wearing a face mask, while 65% of the participants were completely committed to hand washing. The results of the regression analysis revealed that female gender (AOR=1.2; 95% CI: 1.07 - 1.35; p=0.002), having a family member infected with COVID-19 (AOR=8.5; 95% Cl: 7.51 - 9.70; p=0.001), having a health-related work or study (AOR=1.2; 95% Cl: 1.09 - 1.38; p=0.001), believing that face masks do not protect against COVID-19 (AOR=1.3; 95% Cl: 1.12 - 1.47; p=0.001), and partial commitment to handwashing (AOR=1.2; 95% Cl: 1.11 - 1.75; p=0.006) were all associated with an increased odds of contracting COVID-19 among the participants. Conclusion: Overall, commitment to non-pharmaceutical intervention (NPI) measures, such as wearing a face mask, hand washing, and physical distancing, was not optimal among Jordanians. This might explain the dramatic increase in the infectivity rate of the COVID-19 virus in the past few months in the country. More sustainable efforts regarding health promotion and strict policies are required to prevent a third wave of hitting the country and to prevent similar infectious threats in the future.